Variation of UV-A/UV-B daily profiles depending on locations and altitude. Issue 1 (1st January 2023) - Tyutyundzhiev, Nikolay; Angelov, Christo; Arsov, Todor; Nitchev, Hristo; Lovchinov, Konstantin; Mutafov, Asen
Abstract: Solar UV/visible monitoring has increased its importance in the recent years due to the global warming, unexpected atmospheric anomalies and storms, and the increasing needs for additional human protection. In mountain areas with high elevation the interest to UV irradiation measurements is expected to increase due to atmospheric transparency, however frequent events of lightning and risk of equipment failures has to be taken into account. The cost of the UV measurement systems can be greatly reduced by employing low-cost integrated inexpensive digital sensors with on-chip signal conditioning as detectors which are more convenient for field deployment and outdoor measurements. Thus, a compact portable UV/visible sensor equipment is in great demand for annual solar irradiation monitoring and seasonal all-day measurement campaigns. In this work, we report on the development of an in-house portable UV sensor system based on digital sensors with I 2 C communication, open-source hardware and software. The developed equipment is based on integrated digital sensors (VEML 6075, TSL 2591). It has been developed by employing Wi-Fi ESP 32 microcontroller, ODROID microcomputer and open-source software (InfluxDB and Grafana visualization tool). We investigate the system performance by measuring daily profiles of UV-B/UV-A irradiation in different locations and under different atmospheric conditions in order to evaluate its feasibility for prevention of humans from UV overexposure during outdoor operations. On-field tests are performed for 2 years in 7 different locations in Bulgaria. Interestingly, in downtown during particular days with high traffic an increased UV scattering and absorption due to urban pollution has been observed.